ANALISIS IMPLEMENTASI APLIKASI SISTEM TELEMEDICINE “MY GLUCOSE” PADA MASYARAKAT DI WILAYAH GUNUNGPATI SEMARANG - Jariyah, Tata Ainun (Jurnal Pengembangan Rekayasa dan Teknologi, 2022)
AbstractThis study aims to evaluate the implementation of the "MyGlucose" telemedicine system application in the Gunungpati society, Semarang City, which is used to remotely monitor blood sugar levels in diabetic patients as well as oxygen saturation and body temperature. The method used in this research is to develop the MyGlucose application which consists of measuring blood sugar, SpO2, and body temperature connected to the patient's mobile device and software on the health care provider's side. The research sample consisted of 44 respondents who used the MyGlucose application for the last two months. The results showed that the majority of respondents felt that the MyGlucose application was very helpful in monitoring their blood sugar levels independently without having to visit a doctor regularly. This application also assists patients in monitoring blood sugar levels, as well as providing information about health in the article menu available in the application. Therefore, efforts are needed to improve accessibility and education related to the use of the MyGlucose application in the people of the Gunungpati area, Semarang City. In conclusion, the telemedicine system application "MyGlucose" can be an effective alternative in monitoring blood sugar levels, oxygen saturation and body temperature of diabetes patients independently and helping patients consult a doctor without having to go to the hospital.
Keywords: blood sugar; SpO2; body temperature; telemedicine.